Authority of The State Administrative Court In Handling And Resolving Land Cases - Gunawan; Hendri Darma Putra (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
lawsuit/dispute, because this concerns the authority of the judicial body, such as the authority of the State Administrative Court related to handling and resolving land disputes. Therefore, the purpose of this research is to analyze and find out about the authority of the Administrative Court in handling and resolving land cases. This research method is normative juridical. Normative juridical is a method in normative legal research that analyzes secondary data. The secondary data is then analyzed in a qualitative juridical manner. The result of this study are as follows: The authority of the State Administrative Court in handling and resolving land cases is more about the correctness of formal administrative procedures, not authorized to hear “cases of ownership of land rights”, which are civil in nature, even though the land has been certified.